Housing Environment and Farm Animals' Well-Being - Chai, Lilong; Zhao, Yang (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This reprint contains articles from the Special Issue of Animals "Housing Environment and Farm Animals' Well-Being", including original research, review, and communication related to livestock and poultry environmental management, air quality control, emissions mitigation, and assessment of animal health and well-being.